NILAI-NILAI PENDIDIKAN ISLAM DALAM SYAIR NANDUNG INDRAGIRI HULU KARYA AHMAD DARMAWI - Yeri Helfizon; Bustanur Bustanur (Universitas Islam Kuantan Singingi, 2020)
At the present time, mothers are more likely to use radio, television and other electronic media in lulling their children to sleep. And if you pay attention, generally the cassettes that are played are very few values of virtue and even very bad. There are more negative aspects when compared to the positive aspects. His lafadz are also very inappropriate for children who are still in a state of nature.This study is entitled